2015
DOI: 10.3109/15376516.2015.1090514
|View full text |Cite
|
Sign up to set email alerts
|

The evaluate and compare the effects of the Tacrolimus and Sirolimus on the intestinal system using an intestinal cell culture model

Abstract: Tacrolimus (TAC) and Sirolimus (SRL) are produced by Streptomyces sp and effective immunosuppressive drugs commonly used in organ transplantation. Therefore, strategies for minimizing the toxicity of immunosuppressant molecules are our interest. This study was conducted to evaluate the interactive effects and the possible underlying mechanism of TAC and SRL on HCT116 cells. It was found that TAC and SRL alone inhibited cell viability. Also, it induced reactive oxygen species (ROS) formation, loss of mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…However, in the ileum, SRL induced more pathological changes than SRL NCs (e.g., intestinal epithelial inflammatory cell infiltration, congestion, and increased glandular lymphoid follicles) (Figure ). There are some reports that SRL has strong toxicity. , But in the SRL NCs group, there was less direct contact of free drugs with the intestinal mucosa, which explains the lower toxicity . Overall, SRL NCs induced less toxicity and irritation compared with SRL.…”
Section: Results and Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, in the ileum, SRL induced more pathological changes than SRL NCs (e.g., intestinal epithelial inflammatory cell infiltration, congestion, and increased glandular lymphoid follicles) (Figure ). There are some reports that SRL has strong toxicity. , But in the SRL NCs group, there was less direct contact of free drugs with the intestinal mucosa, which explains the lower toxicity . Overall, SRL NCs induced less toxicity and irritation compared with SRL.…”
Section: Results and Discussionmentioning
confidence: 87%
“…There are some reports that SRL has strong toxicity. 49,50 But in the SRL NCs group, there was less direct contact of free drugs with the intestinal mucosa, which explains the lower toxicity. 29 Overall, SRL NCs induced less toxicity and irritation compared with SRL.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Mycophenolate may enhance gut permeability, potentially providing a mechanism for its positive association with TMAO. Furthermore, sirolimus may alter intestinal microbiota composition, induce abnormalities in intestinal barrier function, and cause an increase in circulating proinflammatory cytokines [ 41 , 42 , 43 ]. In humans, sirolimus is metabolized in the intestinal wall and liver, returning from the small intestine to the gut lumen via counter-transport by enterocytes, and can induce mild gastrointestinal side effects [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal permeability is characterized by a loss of the gut epithelial wall integrity allowing different sizes of compounds to enter the systemic circulation (food antigens, commensal or pathogens bacteria, and their metabolites) ( 50 ). By using an intestinal epithelial cell line, Qasim et al have demonstrated the potential of mycophenolic acid to alter tight junction proteins expression and distribution and induce intestinal permeability that may be responsible for gastrointestinal adverse effects observed in transplant patients ( 51 ). This intestinal permeability could also have deleterious consequences such as chronic systemic inflammation ( 52 ).…”
Section: Alterations Of Gut Homeostasis In Solid Organ Transplantationmentioning
confidence: 99%